The Rawlsian principles of justice reconsidered: paper prepared for the 3rd international meeting of the Society for Social Choice and Welfare, Maastricht, 22 - 25 June 1996 - Hans-Peter Weikard (Universität Potsdam, Lehrstuhl Finanzwissenschaft, 1996)
Of Rawls's two principles of justice only the second has received attention from economists. The second principle is concerned with the social and economic conditions in a just society. The first principle, however, has largely been neglected. It claims, that all people in society should have equal basic liberties. In this paper Rawls's first principle is characterised in a freedom of choice framework. The analysis reveals conceptual problems of the Rawlsian approach to justice.
urn:nbn:de:kobv:517-opus-16128
Keywords: D63; 330